2015
DOI: 10.3109/10717544.2015.1030715
|View full text |Cite
|
Sign up to set email alerts
|

Albumin anchored docetaxel lipid nanoemulsion for improved targeting efficiency – preparation, characterization, cytotoxic, antitumor and in vivo imaging studies

Abstract: The aim was to develop albumin anchored docetaxel lipid nanoemulsion (ALNE) for improving tumor targeted delivery. The O/W lipid nanoemulsion, LNEs were prepared by homogenization and ultrasonication processes. The size of globules and zeta potential were measured by Malvern Zetasizer. Albumin was coupled to stearylamine containing lipid nanoemulsion (SALNE) globules using water soluble EDC reaction. The drug content and entrapment efficiencies for the LNEs were determined by the high-performance liquid chroma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Specifically, for improving targeting efficiency, the albumin-anchored docetaxel lipid nanoemulsion is worth mentioning, where both homogenization and ultrasonication are implemented to obtain >80% tumor inhibition. Furthermore, in terms of tumor-targeting activity, >3 times activity was observed compared to only the albumin-anchored stearylamine nanoemulsion as shown in Figure Table shows the drugs with nanoemulsion modification and their cytotoxicity evaluation.…”
Section: Lipid-based Ndds In Cancer Therapymentioning
confidence: 93%
See 2 more Smart Citations
“…Specifically, for improving targeting efficiency, the albumin-anchored docetaxel lipid nanoemulsion is worth mentioning, where both homogenization and ultrasonication are implemented to obtain >80% tumor inhibition. Furthermore, in terms of tumor-targeting activity, >3 times activity was observed compared to only the albumin-anchored stearylamine nanoemulsion as shown in Figure Table shows the drugs with nanoemulsion modification and their cytotoxicity evaluation.…”
Section: Lipid-based Ndds In Cancer Therapymentioning
confidence: 93%
“…With this regard, various types of preclinical and clinical liposome-based glioma therapy strategies have been described by Mojarad-Jabali et al 44 One of the unique applications of liposomes is the imageguided drug delivery that enables both diagnosis and treatment. This has been done by conjugating liposomes with different labeling probes (for example 64 C, 89 Zr, etc.) and guiding the formulations to precise target locations using different modalities such as PET, SPECT, and MRI.…”
Section: Lipid-based Ndds In Cancer Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Using staining with 4′,6-diamidino-2-phenylindole it was found that NEs of GarEO and GarEO-MMC have got attached to the cell membrane causing damage to the cell, while those of ChEO or ChEO-MMC passed the cell membrane and affected the nucleus directly (Alkhatib et al 2018a). In vitro cytotoxicity against MCF-7 and HeLa cells of an albumin anchored docetaxel (DTX) lipid NE was higher than that of the plain NE, and in in vivo experiment it caused 80.01±2.74% inhibition of solid tumours induced in C57BL/6 mice compared to 55.62±5.41% inhibition caused by administration of the plain NE, whereby also its tumour targeting activity was 3-fold higher than that of plain NE (Afzal et al 2016b). Transferrin coupled DTX lipid NE (200−393 nm) prepared by homogenization and ultra-sonication process caused 84.66±4.29% tumor inhibition in tumor induced C57BL/6 mice and was found to have also 3.54-fold higher tumor targeting activity compared to the plain lipid NE (Afzal et al 2016c).…”
Section: Nanoemulsions For Cancer Therapymentioning
confidence: 97%
“…FEO-MMC NE caused also the greatest change on the HeLa cellular morphology, while MCF-7 cells were most damaged and their nuclei were segmented when subjected into high GEO-MMC NE. Consequently, mixing of drug with GEO NE and FEO NE considerably improved its cytotoxicity on the MCF- In vitro cytotoxicity against MCF-7 and HeLa cells of an albumin anchored docetaxel (DTX) lipid NE was higher than that of the plain NE, and in in vivo experiment it caused 80.01±2.74% inhibition of solid tumours induced in C57BL/6 mice compared to 55.62±5.41% inhibition caused by administration of the plain NE, whereby also its tumour targeting activity was 3-fold higher than that of plain NE (Afzal et al 2016b). Transferrin coupled DTX lipid NE (200−393 nm) prepared by homogenization and ultra-sonication process caused 84.66±4.29% tumor inhibition in tumor induced C57BL/6 mice and was found to have also 3.54-fold higher tumor targeting activity compared to the plain lipid NE (Afzal et al 2016c).…”
Section: Nanoemulsions For Cancer Therapymentioning
confidence: 98%